Performance analysis of three-dimensional passive micromixers using k-means priority clustering with AHP-based sustainable design optimization - Syed Farhan Javed; M. Emran Khan; Zeinebou Yahya; M. Javed Idrisi; Worku Tenna (Scientific Reports)
Abstract This novel study presents an in-depth mathematical analysis, investigation, and comparative peculiar assessment of mixing behaviors across different microchannel configurations: the Simple T-shape, Spiral T-shape, and Three-Dimensional Serpentine Passive Micromixer (TDSPM). Considering the pivotal role of micromixing in various applications, the research thoroughly employs the Navier-Stokes equations to analyze flow dynamics and measure the mixing performance of water and water-dye mixtures. The TDSPM, with its distinctive rectangular inlet duct and U-shaped repeating structures, optimizes fluid interaction by constricting flow pathways. The study highlights the superior performance of the TDSPM and thoroughly evaluates the mixing indices for all three micromixer types at Reynolds numbers ranging from 5 to 250. From the priority analysis, Reynolds number (38.49%) and velocity (38.69%) are the most influential factors in micromixer performance, followed by mixing path length (15.35%) and channel width (6.87%). Test 18 (Re = 200, Mixing Path = 25 mm, Velocity = 4.2 m/s, Channel Width = 5 mm) achieves 98% mixing efficiency with a 500 Pa pressure drop, optimizing performance with lower energy costs. Finally, this design leads to remarkable improvements in mixing efficiency over a broad spectrum of Reynolds numbers.